Adaptação para a língua Portuguesa e aplicação de protocolo de avaliação das disartrias de origem central em pacientes com Doença de Parkinson - Fracassi, Angélica Suelen; Gatto, Ana Rita [UNESP]; Weber, Silke Anna Theresa [UNESP]; Spadotto, André Augusto [UNESP]; Ribeiro, Priscila Watson [UNESP]; Schelp, Arthur Oscar [UNESP] (CEFAC Saúde e Educação, 2011)
OBJETIVO: traduzir e adaptar protocolo desenvolvido por pesquisadores alemães, adequando-o às características fonéticas e linguísticas do português falado no Brasil. Caracterizar os componentes de fala mais alterados na população com doença de Parkinson, comparando-os com grupo de sujeitos normais na mesma faixa etária. MÉTODOS: realizou-se a tradução e adaptação do protocolo. Posteriormente foram avaliados 21 pacientes com diagnóstico neurológico de Doença de Parkinson nos estágios Hoehn &Yarh, entre 2 e 3, e 10 sujeitos normais. O protocolo incluía avaliação da respiração, fonação, ressonância, articulação, prosódia e a análise acústica dos parâmetros vocais. RESULTADOS: o protocolo mostrou-se de fácil aplicação clínica. Nos sujeitos com doença de Parkinson foram observadas alterações predominantes na fonação (85,9%) e articulação (42,9%). CONCLUSÃO: o estudo demonstrou ser o protocolo uma ferramenta eficiente para a avaliação da disartria em pacientes com doença de Parkinson.

PURPOSE: to translate and adapt the protocol developed by German researchers, adjusting it to the phonetic and linguistic characteristics of Brazilian Portuguese. Observe the amended speech components in a group of patients with Parkinson's disease, and comparing them with normal subjects in the same age. METHOD: twenty one patients with neurological diagnosis of Parkinson's disease in the Hoehn & Yarh stages (2-3), and 10 control subjects were assessed. The protocol was translated, adjusted and applied to the subjects of both control and Parkinson's disease group, assessing the breathing, phonation, resonance, articulation, prosody and acoustic analysis. RESULTS: in the dysarthria evaluation, the protocol showed to be simple and it presented a fast clinical application. In the subjects with Parkinson's disease, we observed alterations in both phonation (85.9%) and articulation (42.9%). CONCLUSION: the study demonstrated that the protocol is an efficient tool for dysarthria assessment in patients with Parkinson's disease.
Adjustment to the Portuguese and application to patients with Parkinson's disease of protocol within central origin dysarthrias' assessment
Keywords: Disartria; Doença de Parkinson; Avaliação; Dysarthria; Parkinson Disease; Evaluation